Effect of dry-heat and guar gum on properties of egg white powder: Analysis of forming capacity and baking performance. (February 2020) - Chang, Cuihua; Xu, Yali; Shi, Mingcheng; Su, Yujie; Li, Xin; Li, Junhua; Yang, Yanjun
Abstract: The effects of dry-heat treatment (75 °C, 0–20 d) and guar gum (GG) composition on foaming properties and baking performance of egg white powder (EWP) were investigated. Rheological measurement showed that both dry-heat treatment and GG addition can improve the viscosity of EWP dispersion. The particle diameter of EWP dispersion decreased after dry-heat treatment, while hydrophobicity increased, indicating that the increased viscosity was caused by the enhanced hydrophobic interaction rather than particle induced steric hindrance. The sample undergoing 10 days of dry heating with GG addition performed the best foaming properties (foaming capacity 9.37 ± 0.26 mL/g and foaming stability 96 ± 1.56%). However, without GG addition, 10 days of dry heating just induced the foaming capacity and stability increasing from 5.17 ± 0.65 mL/g and 42.85 ± 2.90% to 6.96 ± 0.09 mL/g and 64.95 ± 3.04%, respectively. The sample EWP 10 + GG also exhibited the largest cake specific volume and uniform distribution of foams in cross section, which was observed in all three baking systems (low, middle and high sugar). In low sugar system, GG addition induced an increase in cake specific volume from 3.72 ± 0.02 mL/g to 4.55 ± 0.16 mL/g. The results revealed that combining dry-heat and GG addition can more effectively enhance foaming capacity and baking performance of EWP powder, providing guidance for its efficient application in baking industry. Graphical abstract: Image 1 Highlights: Dry-heat treatment can decrease particle size of egg white powder (EWP) aggregates. Guar gum (GG) addition increases surface hydrophobicity and viscosity of EWP. Addition of GG to dry heated EWP improved foaming properties significantly. EWP with 10 days' dry-heat and GG addition displays the best baking performance.